1993
DOI: 10.2183/pjab.69.255
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase Purified from Alfalfa Infected by Clover Proliferation Mycoplasmalike Organism.

Abstract: Abstract:This study focused on the purification and characterization of chitinase from alfalfa (Medicago sativa L.) infected by CP-MLO. Chitinase (EC 3.2.114) was purified from leaves and shoots of MLO-infected alfalfa plants by ammonium sulfate precipitation, chitin affinity chromatography and Sephadex column chromatography. Three chitinase isoenzymes were identified and shown to have molecular masses of approximately 40, 35 and 30 kilodaltons as determined by SDS-polyacrylamide gel electrophoresis, while onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It is possible that the specific 35 kDa polypeptide from the morphogenic callus of buckwheat represents a chitinase too considering that the family of chitinases has a relatively wide range of molecular weights, from 30 to 40 kDa (Zhong and Hiruki, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the specific 35 kDa polypeptide from the morphogenic callus of buckwheat represents a chitinase too considering that the family of chitinases has a relatively wide range of molecular weights, from 30 to 40 kDa (Zhong and Hiruki, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Plant chitinases have been reported from the roots of yam ( Dioscorea opposite ) (Tsukamoto et al., ), tobacco (Kern et al, ), tomato (Pozo, Azcón‐Aguilar, Dumas‐Gaudot, & Barea, ) and carrot, from stem of sweet potato, cabbage (Chen et al, ) and Crocus sativus (López & Gómez, ), from latex of Ipomoa carnea (Patel et al, ) , Morus alba (Kitajima et al, ) , Ficus microcarpa ((Taira, Ohdomari et al, ), Carica papaya, Ficus carica, Euphorbia characias (Span et al, ) and Hevea brasiliensis (Martin, ), from leaves of tobacco, cotton, tea (Nisha, Prabu, Manda, & Arvinth, ), sugar beet, alfa alfa (Zhong & Hiruki, ), pokeweed (Ohta, Yamagami, & Funatsu, ), potato, Pteris ryukyuensis, beans and oat (Sorensen et al, ), from fruits of Diospyros kaki (Zhang, Kopparapu, Yan, Yang, & Jiang, ) , Punica granatum (Kopparapu, Liu, Yan et al, ) , Ananas comosus (Taira, Ohdomari et al, ) , Ficus awkeotsang (Li, ), wheat and barley grain ( Hordeum vulgare ) (Kragh, Jacobsen, & Mikkelsen, ), barley endosperm, maize kernels (Z ea mays ) (Moore, Price, Boston, Weissinger, & Payne, ) and sweet orange, from seeds of Adenanthera pavonina (Santos et al, ), Astragalus membranaceus (Kopparapu, Liu, Yan et al, ) , Arabidopsis thaliana (Verburg & Huynh, ), Cucumus sativus (Majeau, Trudel, & Asselin, ) , Secale cereale (Yamagami & Funatsu, ), Sorghum bicolor (Krishnaveni, Muthukrishnan, Liang, Wilde, & Manickam, ), Pennisitum glaucum (Radhajeyalakshmi et al, ) , Tamarindus indica (Rao & Gowda, ) , Brassica napus and various beans including faba beans ( Vicia faba ) (S. Wang, Ye, Chen, & Rao, ), canadian cranberry beans ( Phaseolus vulgaris ) (Wang, Shao, Fu, & Rao, ), mung bean ( Phaseolus mungo ) (X. Ye & Ng, ), pea ( Pisum sativum ), black soya bean ( Glycine max ) (Chang et al, ), black soybean seed coat ( Glycine soja ) (Hirano, Hayashi, & Okuno, ), rice bean ( Vigna umbellata ) (Ye & Ng, ), cowpea ( Vigna unguiculata) (Gomes, Oliveira, & Xavier‐Filho, ), lima beans ( Phaseolus limensis ) (Wang, Zhou, Shao, Lu, & Rao, ), moth bean ( Vigna aconitifolia ) (Pareek, Ravi, & Sharma, ) red kidney bean ( Phaseolus vulgaris ) (Mauch & Staehelin, ), chickpea ( Cicer arietinum ) (Nehra, Chugh, Dhillon, & Ranbir, <...>…”
Section: Plant Chitinases (Ec 32114)mentioning
confidence: 99%
“…Plant chitinases are active at a pH range of 4.0–8.0 with an optimum pH of 4.0 for chitinases isolated from Adenanthera pavonina seeds and barley leaf (Kragh et al, ; Santos et al, ). Astragalus membranaceus , sweet potato, rye, alfa alfa, tobacco, tamarind seed chitinases were reported to have an optimum pH of 5.0 (Kopparapu, Liu, Yan et al, ; Rao & Gowda, ; Zhong & Hiruki, ) whereas chitinases from canadian cranberry beans, mung bean, maize kernels, and Ipomea carnea latex exhibited optimum activities at pH 5.4 (Patel et al, ; Wang et al, ; Ye & Ng, ). Some plant chitinase were also optimally active at a pH near about 6 such as chitinases from cabbage stem with roots (Chen et al, ) and tea leaves (Nisha et al, ) as shown in Table .…”
Section: Plant Chitinases (Ec 32114)mentioning
confidence: 99%
See 1 more Smart Citation